2016
DOI: 10.1093/trstmh/trw060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rapid molecular diagnostic tests on time to treatment initiation and outcomes in patients with multidrug-resistant tuberculosis, Tamil Nadu, India

Abstract: Rapid molecular diagnostic tests shortened the time to initiate treatment which was associated with reduced unfavourable outcomes in MDR-TB patients. This supports the policy to scale up these tests in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Even reductions of several weeks or months are likely to significantly impact community transmission 16 and are likely to improve patient outcomes. 12 , 39 This systematic review and meta-analysis has shown that time to treatment is extremely variable and often lengthy. Overall, the average time to treatment from specimen collection was 2.5 months, with a trend towards reduction in delay in more recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even reductions of several weeks or months are likely to significantly impact community transmission 16 and are likely to improve patient outcomes. 12 , 39 This systematic review and meta-analysis has shown that time to treatment is extremely variable and often lengthy. Overall, the average time to treatment from specimen collection was 2.5 months, with a trend towards reduction in delay in more recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular testing methods result in more rapid laboratory turnaround times, 12 , 68–70 and are therefore likely to reduce time to treatment. This was confirmed in our analysis, with genotypic testing resulting in significantly shorter time to treatment than phenotypic methods; our findings are consistent with the results of a randomized trial 71 and a retrospective cohort study published after our search was concluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, a systematic review identified no published evidence linking delay in treatment initiation and MDR-TB outcomes[ 14 ]. Recently, a study from India has reported delayed treatment initiation (>30 days) as a risk factor for unfavourable outcomes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a systematic review identified no published evidence linking delay in treatment initiation to MDR-TB outcomes [ 5 ]. Recently, a study from India has reported delayed treatment initiation (>30 days) as a risk factor for unfavorable outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%